RAS mutation leading to acquired resistance to dabrafenib and trametinib therapy in a multiple myeloma patient harboring BRAF mutation. Issue 1 (6th August 2020) - Le Calvez, Baptiste; Le Bris, Yannick; Herbreteau, Guillaume; Jamet, Bastien; Bossard, Céline; Tessoulin, Benoit; Gastinne, Thomas; Mahé, Béatrice; Dubruille, Viviane; Blin, Nicolas; Antier, Chloé; Theisen, Olivier; et al.
Abstract: Multiple myeloma (MM) is still considered incurable and new therapeutic approaches are therefore needed. Deep‐sequencing analysis revealed the presence of BRAF mutations in up to 15% of patients. The clinical experience of BRAF ‐targeted therapy in myeloma patients harboring BRAF mutation is still limited. We here report the case of a patient with penta‐refractory (bortezomib, lenalidomide, carfilzomib, pomalidomide, and daratumumab) MM with extramedullary BRAF‐mutated disease that achieved clinical response to dual BRAF and MEK inhibition. At the time of disease progression, gene sequencing analysis of the tumor at the time of progression demonstrated a clonal evolution with emergence of a NRAS mutation and persistence of BRAF and TP53 mutations. Backtracking of the NRAS mutation was performed by digital polymerase chain reaction on the baseline biopsy and identified the pre‐existence of the NRAS at a subclonal level. This observation is the first report of acquired NRAS mutation leading to resistance to dual BRAF/MEK inhibitors in MM. These data suggest that a systematic search for RAS mutations using highly sensitive techniques should be performed before considering targeted therapy in relapsed myeloma with BRAF mutation.